2015
DOI: 10.5539/ijbm.v10n6p15
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Firm Performance: The Moderating Role of Reputation and Institutional Investors

Abstract: Drawing on the institutional theory, stakeholder perspective, and ownership literature on corporate social responsibility, this article sheds light on the relationship between the firm social performance and the financial performance of the firm. Singularly, the paper explores a moderating effect of both corporate reputation as a proxy for firm social activities' publicity and the institutional investors in the firm. The paper proposes that expected positive impact of both reputation and institutional investor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 62 publications
1
35
0
2
Order By: Relevance
“…Furthermore, it can be argued that CSR activities in SMEs are informal, ad hoc, usually not reported, and lack visibility; as a result CSR may not have an impact on corporate reputation. However, Fraj-Andrés et al [64] suggested that CSR activities in SMEs contribute to building a better image and strong marketing position which creates a competitive advantage [66]. In addition, Munasinghe and Malkumari [67] pointed out that SMEs are motivated to engage in CSR activities to improve the firm's reputation, employee motivation and economic performance.…”
Section: Corporate Reputationmentioning
confidence: 99%
“…Furthermore, it can be argued that CSR activities in SMEs are informal, ad hoc, usually not reported, and lack visibility; as a result CSR may not have an impact on corporate reputation. However, Fraj-Andrés et al [64] suggested that CSR activities in SMEs contribute to building a better image and strong marketing position which creates a competitive advantage [66]. In addition, Munasinghe and Malkumari [67] pointed out that SMEs are motivated to engage in CSR activities to improve the firm's reputation, employee motivation and economic performance.…”
Section: Corporate Reputationmentioning
confidence: 99%
“…Choongo [22] illustrated that small-and medium-sized enterprises in Zambia can build a good reputation when they actively engage in CSR activities. Likewise, Alshammari [44] contended that CSR contributes to building a better image with stakeholders. Zasuwa [23] also found that CSR activities reinforce consumers' beliefs that the firm is reliable and trustworthy, thereby contributing to building a better corporate reputation.…”
Section: Csr Performance and Foreign Ownershipmentioning
confidence: 99%
“…The work in [25] added evidence on the link between the two constructs being weaker when ownership is more concentrated. The work in [26] also found a moderating effect of ownership structure and corporate reputation. More recently, [4] four that CSP affects Total Factor Productivity (TFP) positively and that 'TFP mediates the CSP-CFP relationship'.…”
Section: Introductionmentioning
confidence: 85%